Osmostoljetni hrvatsko-mađarski suživot - Holjevac, Željko (Array, 2008)
The eight centuries of Croatian-Hungarian coexistence in the frame of a union of states is one of the most interesting historical phenomenon in Europe. The long period of common history is characterised by the mutual interfusion of the two cultures, Croatian and Hungarian. A number of valuable books have already been written about the intertwining of Croatian-Hungarian cultural influence, evident in the heritage of visual arts and architecture, in music, literature, political culture and social and national structures. Among these is a monograph by Doctor of History Dinko Šokčević (born in Budapest in 1960). Croatians and Hungarians are by no means “typical” neighbouring nations.